Usulan Perancangan Perbaikan Proses Bisnis Berbasis Rekonsiliasi Menggunakan Pendekatan Business Process Management (BPM) di PT XYZ - Syahrastani Ayasa; Heriyono Lalu; Sri Widaningrum (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT XYZ is a company engaged in the aircraft maintenance and maintenance industry. In the operational process, it was found that there were problems that occurred in the material procurement business process and the implementation reporting business process where there were differences in actual and system material usage data where 78% of the total recorded material had been used in the system. With these conditions, where the amount of material planned is the same as the data on the amount of material used which is recorded in the system and does not match the amount of material used in its actual condition, the company has the potential to experience material opportunities that are wasted. Thus, a process design is made that aims to harmonize material usage data. Furthermore, root cause analysis is carried out to find out what alternative solutions can be used to solve the problem. Therefore, the 5 Why's Analysis was carried out to obtain the chosen alternative solution, namely the reconciliation process. The design of the reconciliation process is carried out using a Business Process Management (BPM) approach with the Process Design method. Before carrying out the design, it is necessary to determine the specifications and design standards. The design specifications are determined based on the need statement obtained from the interview by the General Manager Purchaser and the design standard used to design this reconciliation process is Minister of Finance Regulation No. 118/PMK.06/2018 concerning Procedures for the Reconciliation Process for State Property. After that, the process of designing the reconciliation process begins with the determination of the process components that are tailored to the need statement, then a reconciliation process flow design is carried out based on standards and adapted to the conditions of the company, after that a Job Description is designed for parties involved in the reconciliation process. From the design process, the design results are obtained in the form of procedures for implementing the material reconciliation process in the procurement business process and business process reporting on project implementation and adding Job Descriptions for parties involved in the business process.